DESIGN OF THE PANCA MASK DOCUMENTARY FILM - I Wayan Dipa Mulyawan; I Nyoman Agus Suarya Putra; I Made Marthana Yusa (Journal of Aesthetics, Design, and Art Management, 2025)
Purpose: This research was motivated by a problem the author discovered in Tulikup Village, Gianyar, namely the Panca Mask Dance, which is usually expressed through "yadnya." To explain this, a documentary film titled "Panca Mask" was designed in Tulikup Village, Gianyar, as a promotional medium to educate the public about the Panca Mask Dance. Research methods: The research methods used by the author include observation, questionnaires, interviews, documentation, and literature studies. The film will utilize production theory through three stages: pre-production, production, and post-production Findings: From the results of the research that has been carried out, it can be concluded that the Panca Mask documentary film contains information that is not widely known by the public. Implications: This film provides benefits and can be further developed and disseminated so that it can be understood by the public, especially the younger generation, in maintaining its existence.